FFS Master Software For Fitness-For-Service Assessment of Hydrogen Induced Cracking Equipment Based on API 579-1/ASME FFS-1 (Fracture and Structural Integrity, 2022)
Over time, industrial equipment, particularly in the oil, gas, and petrochemical industries, is subjected to various forms of degradation and damage that can affect its structural integrity. Most of the Codes and Standards pertaining to components do not address the issues of degradation and damage. As such, performing a Fitness For Service (FFS) assessment is recommended to make run-repair-replace decisions of an in-service component that may be flawed or damaged. In this study, FFS Master –Fitness For Service (FFS) evaluation software –was developed according to the 3rd Edition of the API579-1/ASME FFS-1. The software coding was written using C# programming language with SQL server database. This software is developed specifically for low strength ferritic steel pressurized components with hydrogen induced cracking (HIC), giving the user the ability to accurately assess if system components can continue to operate in their current service condition.
Keywords: Hydrogen Induced Cracking; Hydrogen Damage; API 579-1/ASME FFS-1; Fitness For Services (FFS)